A massive MIMO frame antenna with frequency agility and polarization diversity for LTE and 5G applications. Issue 10 (28th July 2021) - Fakharian, Mohammad M.
Abstract: A switchable antenna array is presented for upcoming 4G/5G massive multiple‐input multiple‐output (MIMO) smartphone applications. The designed antenna is constructed of two modules of the antenna array, namely, a switchable 2 × 2 MIMO 4G antenna module with frequency and circular polarization diversities and a 6 × 6 MIMO 5G antenna module with pattern diversity. Each element in the 4G and 5G modules is fed using by a microstrip line with a tuning slot on the ground plane, consisting of a spiral patch and a short‐ended C‐shaped stab as parasitic element on the non‐metal frame. An area of 22 × 9.3 mm 2 is occupied with each element on the ground plane. Spatial diversity and polarization techniques are used for these antenna elements with the purpose of the reduced coupling effects and enhanced isolation can be achieved. The module of 4G antenna can be work and switch between two operating bands of LTE‐2500 and 5G band by embedding a PIN diode in the structure of antenna element, while the 5G antenna module can be operate in the 3.4–3.6 GHz and could meet the request of upcoming 5G application. The proposed MIMO antenna array is fabricated and tested. Measured isolation of the proposed antenna is more than 15.2 dB in the ON and OFF states of the PIN diodes without applying of any decoupling structures. Furthermore, measured antenna efficiency, radiation pattern, envelop correlation coefficient, and ergodic channel capacity over the desired bands are also verified in this article.